Long-term prognostic value of preoperative anemia in patients with colorectal cancer: A systematic review and meta-analysis. (March 2017) - Wilson, M.J.; van Haaren, M.; Harlaar, J.J.; Park, Hee Chul; Bonjer, H.J.; Jeekel, J.; Zwaginga, J.J.; Schipperus, M.
Abstract: Objective: To evaluate the long-term prognostic factor of preoperative anemia in colorectal cancer patients. Background: Anemia is frequently observed in colorectal cancer patients, with a case incidence of 30 to 67 percent. Besides an indicator of tumor-induced blood loss and inflammation, anemia in cancer is also suggested to be a cause of inferior outcome, possibly via worsening of tumor hypoxia. As surgery is likely to enhance anemia, the long-term prognostic value of preoperative anemia seems most interesting. Methods: Comprehensive searches were carried out in all relevant databases, including MEDLINE, Embase and Web-of-Science. To include studies addressing overall survival, follow-up had to be at least 24 months or till death. For pooling of survival results, a mixed-linear (fixed-effects) model was fit to the reported hazard ratios (HRs) to calculate a pooled estimate and confidence interval. Results: We included 12 studies comprising 3588 patients to estimate the association between preoperative anemia and overall survival (OS) and disease-free survival (DFS). In a fixed-effects meta-analysis of eight studies, including both colon and rectal cancer, preoperative anemia was significantly associated with poor OS (HR 1.56; 95% CI 1.30 to 1.88; p < 0.001). A meta-analysis of seven studies also showed that preoperative anemia was significantly associated with poor DFS (HR 1.34; 95% CI 1.11 to 1.61; p = 0.002). Restricted to studies exclusively on colon cancer or rectal cancer, HRs for OS were 1.25 (95% CI 1.00 to 1.55; p = 0.05) and 2.59 (95% CI 1.68 to 4.01; p < 0.001), respectively, while HRs for DFS were 1.21 (95% CI 0.96 to 1.52; p = 0.11) and 1.61 (95% CI 1.18 to 2.21; p = 0.003). Conclusion: The present meta-analysis reveals that preoperative anemia is significantly associated with decreased long-term OS and DFS in rectal cancer, but not in colon cancer patients, although this meta-analysis is mainly based on retrospective studies with high heterogeneity. These results justify raised awareness about the impact of preoperative anemia on long-term survival. Highlights: Preoperative anemia is an important prognostic factor for long-term OS and DFS in colorectal cancer patients. Raised awareness about the impact of preoperative anemia on long-term survival is required. Preoperative blood management should play a pivotal role in future prehabilitation programs.